Work disrupted opportunity, resilience, and growth in the accelerated future of work - Schwartz, Jeff 1958-; Riss, Suzanne (John Wiley & Sons, Inc., 2021)
"Alarming studies today predict AI and robotics will do away with jobs?but this is only part of the story. Many jobs will change, some jobs will be eliminated entirely, many more jobs will evolve. The new jobs will require new skills and will pay higher wages. This book explains the big picture of this coming global revolution that is redefining how we work. The good news is that we have time to adapt, and the book explains how. The bad news is that doing nothing, will not lead to the results we desire. The book explains what must be done to educate and train people for the changing workplace, and the new paths available to individuals to gain new skills?relevant for all of us who now live longer lives--that include multiple chapters of career reinvention"--
Includes index. - Online resource; title from digital title page (viewed on January 27, 2021)
Keywords: Organizational change; Organizational resilience; Career development; Organizational Innovation; Career Mobility; Changement organisationnel; Résilience organisationnelle; Plan de carrière